Effects of sesamin on chondroitin sulfate proteoglycan synthesis induced by interleukin-1beta in human chondrocytes - Warunee Srisuthtayanont (2018)
© 2017 The Author(s). Background: Numerous studies have reported on the health benefits of sesamin, a major lignin found in sesame (S. indicum) seeds. Recently, sesamin was shown to have the ability to promote chondroitin sulfate proteoglycan synthesis in normal human chondrocytes. This study assesses the anti-inflammatory effect of sesamin on proteoglycans production in 3D chondrocyte cultures. Methods: To evaluate the effects of sesamin on IL-1β-treated human articular chondrocytes (HAC) pellets, the pellets were pre-treated with IL-1β then cultured in the presence of various concentrations of sesamin for 21 days. During that period, the expression of IL-1β, glycosaminoglycans (GAGs) content and Chondroitin sulfate proteoglycans (CSPGs) synthesis genes (ACAN, XT-1, XT-2, CHSY1 and ChPF) was measured. The GAGs accumulation in the extracellular matrix was determined on day 21 by histological analysis. Results: There was clear evidence that sesamin upregulated expression of all the CSPGs synthesis genes, in contrast to the down-regulation of IL-1β expression both in genes and in protein levels. The level of release and matrix accumulation of GAGs in IL-1β pre-treated HAC pellets in the presence of sesamin was recovered. These results correlate with the histological examination which showed that sesamin enhanced matrix CSPGs accumulation. Conclusions: Sesamin enhances CSPGs synthesis, suppresses IL-1β expression and ameliorates IL-1β induced inflammation in human chondrocytes. Sesamin could have therapeutic benefits for treating inflammation in osteoarthritis.